Future of law - "Susskind," (Oxford, 1998)
n this book, Richard Susskind argues that as well as automating and streamlining traditional ways of prividing legal advice, information technology will eventually bring with it major changes in the legal process itself and in the administration of justice. He predicts that the focus of legal services offered on the electronic information highway will be on preempting rather than resolving disputes and on legal risk management rather than legal problem solving. In brief, legal service will emerge as an information service. He points to the kind of social and moral problems in the current system which information technology could overcome, giving details of the enabling techniques which the technology offers to the law. Case studies of operational systems are provided to clarify the arguments presented and Susskind concludes by sketching his vision of the future of law and the attendant implications for its practitioners. He sees the law becoming available and accessible to all. Whilst his arguments bear mainly on Anglo-American common law systems, some of his central themes are relevent also to the European legal tradition.
Keywords: Law and legislation